Forecasting Inflation in Indonesia - Ramakrishnan, Uma.; Vamvakidis, Athanasios (Washington, D.C. : International Monetary Fund, 2002)
A reliable inflation-forecasting model is central for a sound monetary policy framework. In this paper, we study the domestic and international transmission effects on inflation in Indonesia and analyze the possible leading indicators of inflation. We identify the exchange rate, foreign inflation, and monetary growth as the main variables with a significant predictive power for inflation in Indonesia.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet